Polycaprolactone strengthening keratin/bioactive glass composite scaffolds with double cross-linking networks for potential application in bone repair - Liying Sun; Shan Li; Kaifeng Yang; Junchao Wang; Zhengjun Li; Nianhua Dan (Journal of Leather Science and Engineering, 2022)
Abstract In this study, we aimed at constructing polycaprolactone (PCL) reinforced keratin/bioactive glass composite scaffolds with a double cross-linking network structure for potential bone repair application. Thus, the PCL-keratin-BG composite scaffold was prepared by using keratin extracted from wool as main organic component and bioactive glass (BG) as main inorganic component, through both cross-linking systems, such as the thiol-ene click reaction between abundant sulfhydryl groups of keratin and the unsaturated double bond of 3-methacryloxy propyltrimethoxy silane (MPTS), and the amino-epoxy reaction between amino groups of keratin and the epoxy group in (3-glycidoxymethyl) methyldiethoxysilane (GPTMS) molecule, along with introduction of PCL as a reinforcing agent. The success of the thiol-ene reaction was verified by the FTIR and 1H-NMR analyses. And the structure of keratin-BG and PCL-keratin-BG composite scaffolds were studied and compared by the FTIR and XRD characterization, which indicated the successful preparation of the PCL-keratin-BG composite scaffold. In addition, the SEM observation, and contact angle and water absorption rate measurements demonstrated that the PCL-keratin-BG composite scaffold has interconnected porous structure, appropriate pore size and good hydrophilicity, which is helpful to cell adhesion, differentiation and proliferation. Importantly, compression experiments showed that, when compared with the keratin-BG composite scaffold, the PCL-keratin-BG composite scaffold increased greatly from 0.91 ± 0.06 MPa and 7.25 ± 1.7 MPa to 1.58 ± 0.21 MPa and 14.14 ± 1.95 MPa, respectively, which suggesting the strong reinforcement of polycaprolactone. In addition, the biomineralization experiment and MTT assay indicated that the PCL-keratin-BG scaffold has good mineralization ability and no-cytotoxicity, which can promote cell adhesion, proliferation and growth. Therefore, the results suggested that the PCL-keratin-BG composite scaffold has the potential as a candidate for application in bone regeneration field. Graphical Abstract